Subdiaphragmatic Gallstone Mimicking Hepatic Malignancy on FDG PET/CT. (April 2015) - Kim, Jisoo; Siegel, Alan; Yen, Stephanie P.; Seltzer, Marc
<x xml:space="preserve">Abstract</x> Abstract A 70-year-old man underwent an FDG PET/CT for a possible primary liver malignancy or metastasis found on an abdominal MRI obtained as part of a workup for intermittent abdominal pain. The MRI showed an enhancing lesion at the dome of the right lobe of the liver. The lesion was FDG avid with a discrete central calcification. In conjunction with the patient's history of laparoscopic cholecystectomy 1 year prior, the findings were consistent with inflammation around a migrated subdiaphragmatic gallstone. One month after the scan, a CT-guided percutaneous biopsy of this lesion revealed chronic inflammatory cells with no evidence of malignancy.